Transmission of anelloviruses to HIV-1 infected children - Kaczorowska, Joanna; Cicilionytė, Aurelija; Wahdaty, Annet Firouzi; Deijs, Martin; Jebbink, Maarten F.; Bakker, Margreet; van der Hoek, Lia (Frontiers in Microbiology, 2022)
Anelloviruses (AVs) are widespread in the population and infect humans at the early stage of life. The mode of transmission of AVs is still unknown, however, mother-to-child transmission, e.g., via breastfeeding, is one of the likely infection routes. To determine whether the mother-to-child transmission of AVs may still occur despite the absence of natural birth and breastfeeding, 29 serum samples from five HIV-1-positive mother and child pairs were Illumina-sequenced. The Illumina reads were mapped to an AV lineage database “Anellometrix” containing 502 distinct ORF1 sequences. Although the majority of lineages from the mother were not shared with the child, the mother and child anellomes did display a significant similarity. These findings suggest that AVs may be transmitted from mothers to their children via different routes than delivery or breastfeeding.